PATENTS STUDY ON THE USE OF SUGARCANE BIOMASS IN ENERGY GENERATION - González Cabrera, Odonel; Ruiz Pérez, Taimi (Centro Azúcar Journal, 2026)
Introduction: Patents protect all solutions given worldwide to technical problems in all branches of technological knowledge. On the other hand, there are numerous applications of sugar cane waste and other by-products of the sugar industry to generate electricity. It is a form of renewable energy that has proven to be a sustainable and economical alternative. Objective: To evaluate the solutions offered in patent literature for their possible use in electricity generation using sugarcane biomass. Materials and Methods: The patent database selected for the study was Patenscope. It was determined to create a strategy that would cover the largest number of patents on the subject in question. An advanced search was used that related the terms selected in the English claim field. A group of patentometric indicators were extracted, whose base is mainly quantitative, established by statistical counts and frequency counts. Results and Discussion: The results of indicators are presented: evolution of the subject over time, number of patents by country, companies and technological subjects. Specific documents are also identified that are essential for the development of technologies in the field of study in question. Conclusions: The patent study identifies solutions for the generation of energy from sugarcane biomass. With its statistical processing, several advantageous patentometric indicators can be obtained for technological and prospective surveillance, which can also be assimilated by the Cuban industry.